Competencies in the Workplace of the Bachelor of Science in Fisheries Graduates of the Western Philippines University - Elsa Carmen N. Montano; Nelson S. Salvador (Philippine Association of Institutions for Research, Inc., 2012)
This study was conducted to assess the Bachelor of Science in Fisheries' graduates competencies and how they fare in their job as assessed by the employers. The study employed the descriptive survey and correlational methods of inquiry using a prepared questionnaire that involved 46 graduates. The data gathered were statistically treated and analyzed with the use of frequency, percentages, mean, ranking, weighted mean, Chi-square and Cramer's coefficient. Results revealed that most of the graduates were employed in the government agencies. The graduates' competencies were indicative that they can work with others. Employers confirmed the graduates are capable and very prepared for work. A Significant association existed between the graduates' nature and status of employment in terms of present employment status, place of work and employing skills and their professional preparation as to reasons for taking the course. The employers' assessment of the graduates in terms of their job performance, quality of graduates being employed, employment skills and other skills were significantly associated to the graduates reasons for taking the course. The study concluded that graduates nature and status of employment are the results of their professional preparation.